An analysis of spatial and temporal variation of net primary productivity over Peninsular Malaysia using satellite data - Ibrahim, Ab. Latif; Okuda, Toshinori; Faidi, Mohd. Azahari (National Institute for Environmental Studies, Japan, 2006)
The main objective of this study is to carry out further analysis of Net Primary Productivity of Malaysia forest using three different types of satellite data; (i)NOAA AVHRR, (ii)MODIS, and (iii)Landsat-TM. The spatial and temporal distribution of NPP over Malaysia forest was analyzed using NOAA satellite images and MODIS data, while analysis of Landsat TM data was used to make a detailed analysis of NPP for forested area in the state of Pahang. Seasonal values of NPP were analyzed using NOAA AVHRR data acquired in the year 2004. Results indicate that the highest value of NPP is for the month of April 301.65 301.65 gCm2month-1 followed by October with 217.78 gCm2month-1, January (189.6 gCm2month-1) and July (89.22 gCm2month-1). NPP maps showing seasonal and spatial pattern were also produced using Geographical Information System (GIS).